Análise climatológica da incidência de chuva no município de Altamira-PA, no período de 1981 a 2011 - MAGANO JÚNIOR, Haroldo (2019)
The present paper is a study of the climatological annual variability, and monthly timemonthly of rainfall in the city of Altamira, PA. Was analyzed the distribution of timemonthly cumulative frequency, quarterly frequency of hourly precipitation and monthly standard deviation of rainfall. For this work we used rainfall data from 1981 to 2011, totaling 31 years of rainfall data, these data are as cumulative from 09:00 until 21:00 local time and 21:00 to 09:00 local time the following day. The analysis showed that the city of Altamira-Pa rain on average 2085 mm per year, more may exceed 2500 mm, with the wettest period is from December to May. The analysis showed that in the city,of Altamira-Pa on average 2085 mm rain per annum, sometimes exceeding 2500 mm, and the rainy season lasts from December to May, corresponding to 82% of annual rainfall in the region and less rainy from June to November, accounting for 18% of the rain. The climatology shows that rainfall has a significant annual variability being mainly influenced by the standards of the Atlantic dipole and ENSO phenomena, being mainly influenced by the standards of the Atlantic dipole and ENSO phenomena. It was also found that the occurrence of most of the annual rainy period is from 21 hours up to 09 hours, where greater than 250 mm rains are more frequent in the first and second quarter, also having a high standard deviation in this period, featuring well the maximum performance of the ITCZ and the LIs over the region.